SORPTION-DESORPTION-PHOTOMETRIC DETERMINATION OF IRON IN SULPHOSALYCYLIC ACID WITH USE 3-(METHYLAMMONIUM)-PROPHYLSILICA: UDC 543.062+541.183+546.72+547.587.11 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The influence of pH, the concentration of sulfosalicylate-, sulphate- and chloride-ions on fullness of sulfosalicylate complexes of iron(III) sorption has been studied. A reagent-free sorption photometric method for determining trace iron(III) in sulfosalicylic acid was developed. The method consists in the selective sorbtion of iron(III) sulfosalicylate complexes on 3-(methylammony)-propyl silica at pH 5-8 followed by the elution of complexes with 0,20 M nitrate acid and measurement of the absorbance of eluates with adds of ammonia. The analytical range for iron was 1,7–20 mg in a 0,50–0,63 g of a sample. The determination level and relative standard deviation were 2,8×10–4 % and 8,1 %, respectively (n=3 і P=0,95).
Keywords: -